Дворянское гнездо: 1858-1860 / [примечания М. П. Алексеева] - Тургенев Иван Cергеевич (1981)
Экземпляры: Селтинская районная библиотека (к/х) (20201207) / Инвентарный номер: 39697 / Авт.знак: Т 87 / ГРНТИ: 17.82 / ББК: 84(2=411.2)